2016
DOI: 10.1109/jsyst.2014.2363161
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Resilient Holistic Supply Chain Network System: Concept, Review and Future Direction

Abstract: The recent financial crisis and other major crises have suggested that there are some strong interactions and interdependence between several supply chains and their external environments in various ways. A set of supply chains that are interdependent is called a holistic supply chain network (H-SCN) in this paper. There is a need to focus on building the resilience (in short, the ability of a system to recover from damage or disruption) of an entire H-SCN as it is believed that such a network system is strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(53 citation statements)
references
References 145 publications
0
51
0
2
Order By: Relevance
“…Pereira et al (2014) systematically reviewed research on SCR, identified various enablers and barriers but restricted the analysis to the upstream side of the supply chain, particularly the procurement function and how it could impact the resilience of the supply chain. Wang et al (2016) reviewed SCR using systems theory while Hohenstein et al (2015) adopted the sand cone model to develop a comprehensive SCR framework after reviewing 67 peer-reviewed articles from 2003 to 2013. This paper identified SCR elements and grouped them under proactive and reactive strategies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pereira et al (2014) systematically reviewed research on SCR, identified various enablers and barriers but restricted the analysis to the upstream side of the supply chain, particularly the procurement function and how it could impact the resilience of the supply chain. Wang et al (2016) reviewed SCR using systems theory while Hohenstein et al (2015) adopted the sand cone model to develop a comprehensive SCR framework after reviewing 67 peer-reviewed articles from 2003 to 2013. This paper identified SCR elements and grouped them under proactive and reactive strategies.…”
Section: Introductionmentioning
confidence: 99%
“…However, a few previous studies have applied various theories in examining SCR. For example, Ponomarov and Holcomb (2009), Blackhurst et al, (2011) and Brusseta and Teller (2017) Page 2 of 48 Supply Chain Management: an International Journal p p l y C h a i n M a n a g e m e n t : a n I n t e r n a t i o n a l J o u r n a l 2 adopted the resource-based view theory, Spiegler et al (2012) and Wang et al (2016) used the systems theory while Day (2014) and Tukamuhabwa et al (2015) used complex adaptive systems. However, no research has thus far explored the usefulness of the Cynefin framework and/or High Reliability Theory in SCR research.…”
Section: Introductionmentioning
confidence: 99%
“…We provide a comprehensive literature review in this section, along with categorization and analysis of these methods. Firstly, a systematic literature search (adapted from Wang et al (5) and Wang et al (31) ) was conducted in two databases, Scopus and Web of Science. The search code was as follows: TITLE (robustness) and TITLE-ABS-KEY (transportation or road or subway or highway or rail or airline or bus or waterway) and TITLE (network or system) and PUBYEAR > 1999 and DOCTYPE (ar OR re) and (LIMIT-TO [LANGUAGE, "English"]).…”
Section: Methodology Of Literature Reviewmentioning
confidence: 99%
“…This ecology-based definition of resilience forms the basis of resilience work in the fields of information and communication sciences (Laprie, 2008) and manufacturing supply chain resilience (Zhang and Van Luttervelt, 2011). As reviewed by Wang et al (2016), most of the studies dealing with supply chain resilience have concentrated on the abrupt disruptions in the supply chains of firms or products. These types of studies address financial or commercial risks arising from poor quality or sub-optimal supply chains and follow a qualitative methodology, or use a quantitative simulation-based framework that incorporates concepts of resilience into the process of supply chain design (Craighead et al, 2007;Huang et al, 2007;Sheffi and Rice, 2005;Christopher and Peck, 2004).…”
Section: Introductionmentioning
confidence: 99%